Music video: evaluation of communication media for health campaign in early childhood education and development (ECED) students - Vina Mahdalena; Lusia Handayani (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
The media for health campaigns carried out by both the government and the private sector are very diverse. This shows the importance of selecting and packaging media at the planning stage. The purpose of this research is to create a music video which suitable for the target audience (Early Childhood Education and Development Students) to campaign for the 7 steps of hand hygiene. The method is a type of Research and Development (R & D) which focuses on the process to produce the music video. Development models in this research is procedural which consider with suitable objectives to be achieved. The results of the feasibility tested by material experts were 89.9%, media experts were 89.7% and ECED students were 97.1%. From the percentage of the evaluation test, it can be concluded that the music video media produced in this study are appropriate to be used as a health campaign tool for ECED students and can be disseminated for the benefit of the community. So, the music video design has been proven to ECED students as a communication media campaign of 7 steps hand hygiene.